2017
DOI: 10.3897/mycokeys.22.12528
|View full text |Cite
|
Sign up to set email alerts
|

Kalbionora palaeotropica, a new genus and species from coastal forests in Southeast Asia and Australia (Malmideaceae, Ascomycota)

Abstract: A new species and genus, Kalbionora palaeotropica, is described for a crustose lichen occurring in coastal forests in Thailand, Vietnam, and northeastern Australia. It is morphologically similar to Malmidea and Eugeniella, but differing in morphological and chemical characters. The single known species in the new genus contains atranorin, zeorin, the stictic acid chemosyndrome and chlorinated xanthones. Morphologically it is characterized by having asci of the Catillaria-type, a yellowish brown colour, a granu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…10), as well as a specimen of Lecidea malmeana from GLBA. However, the genus Kalbionora , which has been postulated to belong to Malmideaceae (Sodamuk et al 2017), did not cluster with this family in our phylogenetic analyses. Many more lichen-forming genera and species need to be sampled to paint a more complete picture of phylogenetic relationships in Malmideaceae .…”
Section: Descriptions Of New Genera and Speciesmentioning
confidence: 61%
See 1 more Smart Citation
“…10), as well as a specimen of Lecidea malmeana from GLBA. However, the genus Kalbionora , which has been postulated to belong to Malmideaceae (Sodamuk et al 2017), did not cluster with this family in our phylogenetic analyses. Many more lichen-forming genera and species need to be sampled to paint a more complete picture of phylogenetic relationships in Malmideaceae .…”
Section: Descriptions Of New Genera and Speciesmentioning
confidence: 61%
“…Despite the lacunose sequence coverage, we recovered the Malmideaceae as a well-supported, monophyletic clade including L. albofuscescens as well as Lecidea malmeana , a polysporous species collected in GLBA. Of species that have been previously reported to belong to Malmideaceae , only Kalbionora (Sodamuk et al 2017) was not recovered within this clade, instead grouping in an unsupported relationship with the outgroup Rhizocarpon . We refrain from undertaking any nomenclatural changes because of poor internal support within Malmideaceae , and ongoing studies.…”
Section: Resultsmentioning
confidence: 81%
“…In fact, only recently the genera Crustospathula, Kalbionora , and Sprucidea have been recognized to be part of Malmideaceae (Cáceres et al 2017; Sodamuk et al 2017), in addition to the originally included species of Malmidea, Savonorala , and two taxa of Lecidea s. lat. (Kalb et al 2011; Ertz et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies on the Malmideaceae have indicated that the ascus and ascospore structures vary between the different genera (Cáceres & al., 2017). The family Malmideaceae has lately been investigated in more detail and several new genera have been described (Cáceres & al., 2017;Muggia & al., 2017;Sodamuk & al., 2017). Further molecular studies with a dataset including sequences of all known Malmideaceae genera are necessary to find out whether all species from clade A belong into this family and whether they form distinct genera.…”
Section: Version Of Recordmentioning
confidence: 99%